Can Companies Maintain their Initial Innovative Thrust? A Study of the PC Software Industry - Prusa, Thomas J.; Schmitz, James A. (The Review of Economics and Statistics, 1994)
Thomas J. Prusa, James A. Schmitz, Jr., Can Companies Maintain their Initial Innovative Thrust? A Study of the PC Software Industry, The Review of Economics and Statistics, Vol. 76, No. 3 (Aug., 1994), pp. 523-540